2011
DOI: 10.1007/s11832-010-0310-6
|View full text |Cite
|
Sign up to set email alerts
|

Early experience with medial femoral tension band plating in idiopathic genu valgum

Abstract: PurposeFor correction of angular deformity, tension band plating has been proposed as a safe and minimally invasive technique. The purpose of this study was to assess the experiences and report the rate of correction obtained with this procedure in patients with idiopathic genu valgum.MethodsThis study was a retrospective review of 47 valgus deformities of the knee treated with medial hemiepiphysiodesis using a tension band plate. The tibiofemoral angle (TFA) and the anatomic lateral distal femoral angle (aLDF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 20 publications
3
25
0
1
Order By: Relevance
“…6,7 At correction, the angles had improved to a mean of 9.56° and 5.72° (Table-2 In a study conducted by Guzman et al, the TFA had improved from a pre-operative mean of 11.2° to 6° at correction and the mean LDFA improved from a preoperative mean of 77.5° to 88.14° at correction. 8 In our study, the tibio-femoral angles had improved from 16.1° to 4.67° post-operatively. Mean LDFA had improved from 77.5° pre-operatively to 88.14°at correction.…”
Section: Discussionsupporting
confidence: 53%
“…6,7 At correction, the angles had improved to a mean of 9.56° and 5.72° (Table-2 In a study conducted by Guzman et al, the TFA had improved from a pre-operative mean of 11.2° to 6° at correction and the mean LDFA improved from a preoperative mean of 77.5° to 88.14° at correction. 8 In our study, the tibio-femoral angles had improved from 16.1° to 4.67° post-operatively. Mean LDFA had improved from 77.5° pre-operatively to 88.14°at correction.…”
Section: Discussionsupporting
confidence: 53%
“…Schroerlucke et al [14] reported that eight failures occurred in patients with Blount disease and involved breakage of the tibial metaphyseal screw in the proximal tibia. Other authors have reported infections [11,17], knee effusion [17], rebound deformity, or uncorrected deformity [11,12,18,19]. These failures were more likely to occur in overweight or obese patients with Blount disease and more likely in the metaphyseal screw with resultant screw failure.…”
Section: Discussionmentioning
confidence: 97%
“…4 Physiological GV in childhood have IMD of up to 8cm, the greatest distance being observed between 3 and 4 years, 5 disappearing gradually after the age of 7-8 years. 6 If the longitudinal axis of the knee joint is not aligned by then, and the IMD is more than 5cm, 7 physiotherapeutic intervention is called for. The degree of GV has a significant effect on the development of growing pains 8 and orthrosis because the imposed loads are no longer equally distributed between the outer and the inner halves of the knee.…”
Section: Introductionmentioning
confidence: 99%